(3TQM JgPjH GdYdGeI ddYejOjs - (3MSjf GdYejOj GdfLajs
(3ChdgG (B:s
.. (3GdePchQ HYde hGLH GdhLhO hYde GdedGFcI hGdfHj U hYde GdebdO CjVG EdG Cf GdebdO CjVG jSJOd Ydi Yjf cd Mce HYdI JbdjOG HCfg CaJGg GdeaJj hcd eG CaJGg Hg GdeaJj agh Mce Gddg JYGdi aj Mbg hEf cGfJ UhQI Odjdg aj Gdcd hGMOI (B...s
(3BNQgG (B:s
.. (3hjQi GLJeGY GdfGS Ydjg hGdYed HaJhGg hGdGfbjGO Edi bhdg hGdYed HebJVGg hGbHGd GdeSdejf Ydi SDGdg hGSJQTGOg hJYXjeg hEcQGeg hdG jLhR ddYGej JbdjO ef jXfg NGdjG ef GdYde hGdOjf (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B13\566s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs